“Ngeroncongi Sunda”: Sundanese Vocal Ornamentation and Hybrid Aesthetics in Indonesian Keroncong Ekstra - Uus Karwati; Febbry Cipta; Diah Latifah; Marsel Ridky Maulana (Harmonia: Journal of Arts Research and Education, 2026)
Keroncong music represents one of Indonesia’s most valuable artistic heritages, embodying the nation’s history, culture, and musical identity. Meanwhile, kawih, a traditional Sundanese vocal genre, features distinctive vocal ornaments derived from kepesindenan and Tembang Sunda Cianjuran, including an aesthetic element known as dongkari. This study aims to integrate Sundanese vocal ornamentation with keroncong vocal style to create a new form of musical expression that remains rooted in tradition. This study employed a descriptive qualitative approach, encompassing stages of song and vocal ornament transcription, classification of ornament types and techniques, and performative analysis of kawih songs performed in the keroncong ekstra rhythm. The findings reveal that the vocal techniques of kawih and keroncong ekstra share similarities in breath control and dynamics, yet differ in vocal timbre, with resonance centered and supported by head and nasal resonance. Diction and articulation adhere to the Sundanese dialect, while expression aligns with lyrical meaning and melodic texture. The identified ornaments include reureueus, riak, beulit, kait, jekluk, dorong, leot, gibeg, buntut and golosor, all performed improvisationally. Overall, the integration of Sundanese vocal ornamentation within keroncong ekstra enriches the aesthetic color and opens possibilities for the development of hybrid art that represents a dialog between tradition and innovation. It is recommended that future research focus on strengthening vocal scholarship to advance technique, aesthetics, and musical expression, thereby enhancing global competitiveness.